Gender identity, sexual orientation, and sexual assault: challenging the myths - Schulze, Corina (Lynne Rienner Publishers, 2019)
Understanding sexual violence: challenging the myths -- The importance of identity -- Sexual assault and disclosure -- Rape myths and rape culture -- The identity inclusive sexual assault myth scale -- Unique concerns and resources -- What have we learned?